Book Review: Understanding the Social Economy: A Canadian Perspective - Weaver, Robert (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2013)
Jack Quarter, Laurie Mook, and Ann Armstrong. Toronto: University of Toronto Press, 2009.